Contrast-enhanced perfusion magnetic resonance imaging for head and neck squamous cell carcinoma: A systematic review. Issue 2 (February 2015) - Noij, Daniel P.; de Jong, Marcus C.; Mulders, Lieven G.M.; Marcus, Johannes T.; de Bree, Remco; Lavini, Cristina; de Graaf, Pim; Castelijns, Jonas A.
Summary This systematic review gives an extensive overview of the current state of perfusion-weighted magnetic resonance imaging (MRI) for head and neck squamous cell carcinoma (HNSCC). Pubmed and Embase were searched for literature until July 2014 assessing the diagnostic and prognostic performance of perfusion-weighted MRI in HNSCC. Twenty-one diagnostic and 12 prognostic studies were included for qualitative analysis. Four studies used a T2∗ sequence for dynamic susceptibility (DSC)-MRI, 29 studies used T1-based sequences for dynamic contrast enhanced (DCE)-MRI. Included studies suffered from a great deal of heterogeneity in study methods showing a wide range of diagnostic and prognostic performance. Therefore we could not perform any useful meta-analysis. Perfusion-weighted MRI shows potential in some aspects of diagnosing HNSCC and predicting prognosis. Three studies reported significant correlations between hypoxia and tumor heterogeneity in perfusion parameters (absolute correlation coefficient |ρ| > 0.6, P < 0.05). Two studies reported synergy between perfusion-weighted MRI and positron emission tomography (PET) parameters. Four studies showed a promising role for response prediction early after the start of chemoradiotherapy. In two studies perfusion-weighted MRI was useful in the detection of residual disease. However more research with uniform study and analysis protocols with larger sample sizes is needed before perfusion-weighted MRI can be used in clinical practice.